RETRACTED: Methods of using STEAM technologies in the development of pupils’ computational thinking - Akramova Gulbahor; Ma’murov Bahodir; Akramova Surayo; Qo’ldoshev Rustambek; Shodmonova Abera (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001